ANEMIA PREVENTION COUNSELING FOR PREGNANT WOMEN AND PA'DE SUKMA INNOVATION (ANEMIA PREVENTION WITH DATE MILK) FOR PREGNANT WOMEN AT UPTD PUKES CENTER BATUJAYA - Kundaryanti, Rini; Kaswati, Dedeh; Dian Permatasari, Dessy; Zulpia, Ida Farrida; Karyanah, Karyanah; Cahaya Utami, Rita; Taubah, Rosita; Amnah, Siti (HEARTY, 2025)
Anemia is a public health nutrition problem, especially in pregnancy with hemoglobin levels of less than 11 gr / dl. Efforts to improve maternal health by preventing maternal mortality are issues of concern at the national and global levels, because maternal health is the key to the welfare of children in the future. This community service activity aims to increase the knowledge of pregnant women about anemia in pregnancy and improve the attitudes of pregnant women so that they can realize the importance of preventing and treating anemia in pregnancy. This activity was carried out through the implementation of a simulation of the use of date milk and small group discussions on anemia involving 10 pregnant women from the Batujaya Health Center Area, Karawang Regency. The minimum knowledge score between before and after the activity increased significantly, from the lowest score of 30 to the lowest score of 70, and from the highest score of 70 to the highest score of 100. Most respondents strongly agreed that anemia can endanger pregnancy, so respondents also strongly agreed that efforts to prevent anemia need to be done. carried out including through the consumption of blood-boosting tablets and quality nutrition. Positive activities outside of pregnancy visits to health workers can be a medium for getting support and a place to share between pregnant women with each other, this has the potential to increase the knowledge and attitudes of pregnant women about preventing anemia in pregnancy.